Recommendations for the prevention and treatment of hepatitis B and C infection in patients on the waiting list for liver transplantation and in liver transplant recipients - M. Sh. Khubutiya; S. E. Voskanyan; V. E. Syutkin; V. P. Chulanov; M. S. Novruzbekov; V. D. Pasechnikov; V. L. Korobka; O. O. Rummo; E. N. Bessonova; S. F. Bagnenko; D. I. Abdulganiyeva (Трансплантология (Москва))
.